Roland Morris Disability Questionnaire in Bengali for Evaluation of Patients With Low Back Pain (KYAMC Journal, 2020)
Background: Low back pain (LBP) has been identified as one of the most frequent, disabling and costly condition which create a significant clinical and socioeconomic burden on national economy. The Roland Morris Disability Questionnaire (RMDQ)is one of the most commonly used outcome measures in patients with LBP.Objectives: To develop a culturally adapted Bangla version of RMDQ and to test its reliability and validity in patients with low back pain.Materials and Methods: This observational study was carried out from September 2015 to August 2016. The US English RMDQ was translated into Bangla after established crosscultural adaptation procedures, recommended by Beaton et al. Reliability was assessed by using internal consistency (Cronbachs' alpha coefficient) and inter-rater reliability (the intra-class correlation coefficient - ICC). The Content validity was evaluated by three expert Physiatrists and construct validity was tested by association with the physical functioning (PF-10) subscale of 36-items short form health survey (SF-36).Results: 100% participants had responded to all items of RMDQ. It was found to have 100% content validity. 50 % respondents did not have any difficulty in understanding the Bangla RMDQ and 30% faced difficulty in understanding in 1 item and 20% faced difficulty in 2 items (n=30). The values of Cronbachs' alpha coefficient and ICC were 0.89 and 0.95 respectively. Bangla RMDQ showed good correlation (r=-0.81) with Physical Functioning (PF-10) subscale of SF-36 in assessing construct validity.Conclusion: Bangla RMDQ appears to be an acceptable, reliable, and valid instrument for assessing disability in patients with LBP.KYAMC Journal Vol. 11, No.-1, April 2020, Page 21-25